(untitled) (Western European Journal of Medicine and Medical Science, 2024)
The purpose of this article is to describe congenital heart defects, to study their causes and to provide information about accurate and rapid diagnostic diagnosis and treatment methods of these defects with the help of improved devices available in modern medicine .